3D chiral and 2D achiral cobalt(ii) compounds constructed from a 4-(benzimidazole-1-yl)benzoic ligand exhibiting field-induced single-ion-magnet-type slow magnetic relaxation. Issue 18 (7th April 2016) - Wang, Yu-Ling; Chen, Lin; Liu, Cai-Ming; Du, Zi-Yi; Chen, Li-Li; Liu, Qing-Yan
Abstract : A 3D chiral and a 2D achiral cobalt(ii ) compounds displaying field-induced slow magnetic relaxation resulting from single-ion anisotropy of the individual Co(ii ) ions are presented. Abstract : Organizing magnetically isolated 3d transition metal ions, which behave as single-ion magnet (SIM) units, in a coordination network is a promising approach to design novel single-molecule magnets (SMMs). Herein 3D chiral and 2D achiral cobalt(ii ) coordination compounds based on single metal nodes with a 4-(benzimidazole-1-yl)benzoic acid (Hbmzbc) ligand, namely, [Co(bmzbc)2 (1, 2-etdio)] n (1 ) (1, 2-etdio = 1, 2-ethanediol) and [Co(bmzbc)2 (Hbmzbc)] n (2 ), have been synthesized and structurally characterized. The 3D chiral structure1 with 2-fold interpenetratingqtz topological nets consisting of totally achiral components was obtained via spontaneous resolution, while the achiral structure2 is a 2D (4, 4) net. In both structures, individual cobalt(ii ) ions are spatially well separated by the long organic ligands in the well-defined networks. Magnetic measurements on1 and2 showed field-induced slow magnetic relaxation resulting from single-ion anisotropy of the individual Co(ii ) ions. Analysis of the dynamic ac susceptibilities with the Arrhenius law afforded an anisotropy energy barrier of 16.8(3) and 31.3(2) K under a 2 kOe static magnetic field for1 and2, respectively. The distinct coordination environments of the Co(ii ) ions in1 and2 lead to the different anisotropic energy barriers.